Research Trends on Small-Sided Games in Soccer: A Bibliometric Analysis (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2025)
A valid, credible, and comprehensive literature meta-study determines the level of accuracy in diagnosing previous research findings. It determines the development of more meaningful and useful future research. The purpose of this study was to examine the development of research articles on small-sided games in soccer. This study is quantitative research with bibliometric study method. Data were collected using the Publish or Perish application applying keywords "small-sided games in soccer" and "small sided games" for articles published in the last 10 years (2014-2024). The collected data were verified using Mendeley and analyzed using the VOSviewer tool. The results of the examination found that research on the small-sided game model had not experienced significant development. It was because most of the 163 papers analyzed still discussed training models for mastering and improving physiology aspects, biomotor, techniques, and soccer tactics. Future research is needed to develop a small-sided game training model that complements mental or character values, including perseverance, discipline, teamwork, and respect. This study contributes as an evaluation of the small-sided game model article publication database that can be used by advanced researchers to create more significant future research on more impactful, meaningful, and futuristic training models for young athletes to become elite athletes with strong character.